On the diversity of abyssal Dondersiidae (Mollusca: Aplacophora) with the description of a new genus, six new species, and a review of the family - Cobo, M. Carmen; Kocot, Kevin M. (Zootaxa, 2021)
So far, of the 292 known species of solenogasters (Mollusca, Aplacophora), 62 belong to the clade Pholidoskepia Salvini-Plawen, 1978. Of these, only two have an abyssal distribution (3500–6000 m depth). Among Pholidoskepia, Dondersiidae Simroth, 1893 is the most diverse family. This study contributes to the knowledge of this family with the description of one new genus and six new species from the abyssal South Atlantic Ocean: Dondersia ? foraminosa sp. n., Nematomenia divae sp. n., Nematomenia brasiliensis sp. n., Nematomenia ? guineana sp. n., Helluoherpia vieiralaneroi sp. n. and Inopinatamenia (gen. n.) calamitosa sp. n. Specimens were collected during DIVA (Latitudinal Gradients of Deep-Sea BioDIVersity in the Atlantic Ocean) expeditions in the Guinea (DIVA 2 Me 63/2, 2005) and Brazil (DIVA 3 Me 79/1, 2008) Basins. Specimens were characterized based primarily on the sclerites and internal anatomy, which was studied using histology. The importance of the radula and mantle sclerites for taxonomy is emphasized. Amended diagnoses for the family and some genera within this family are provided. This contribution increases the described diversity of Dondersiidae to ten genera and 38 species and highlights the need for more study of solenogasters in the deep sea.